ANALISIS INDEPENDENSI ODITUR MILITER DALAM MELAKSANAKAN FUNGSINYA DI ODITURAT MILITER III-14 DENPASAR DENGAN BERLAKUNYA KEBIJAKAN RENCANA TUNTUTAN - Wahyudi, Misran (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 4 No 3 (2015)DO - 10.24843/JMHU.2015.v04.i03.p08, 2015)
Military Prosecuting Attorney is one of the main components in enforcing the criminal law in the military judicature system. Moreover, the Military Prosecuting Attorneys is as a prosecutor in the Indonesian National Armed Forces (TNI). Confidently, it has major function in demanding based on legitimating evidences in military court. Military Prosecuting Attorney can work its duty well, if it has independently in the function as general presector of Indonesian military court system. Afterwards, the first problem is wheter Military Prosecuting Attorney independently achieve its function in Oditurat Militer III-14 Denpasar by conducted the plan demans policy as of Military Prosecuting Attorney General Indonesian National Armed Forces? Whereas, the second problem is whether the efforts shoud be accomplished in establishing independent Military Prosecuting Attorney? This research was conducted by empirical legal research methods, and the study was a descriptive analytic research by using primary data and secondary data. Based on this research, it can be concluded that; first, Military Prosecuting Attorneys in Oditurat Militer III-14 Denpasar became less independent, it was occured because the implementation of the plan demand policy by Military Prosecuting General Attorney. It can be stated that the demand was only established by upper position and finally, the judgments are not merely according conscience. Secondly, Military Prosecuting Attorney attempt to independently in military justce system in three aspects such as technical field of prosecution, field supervision and control, as well as education and training.
Keywords: Military Prosecuting Attorneys, Independence, Functions